Diagnosis and Management of Peritoneal Metastases from Ovarian Cancer - Evgenia Halkia; John Spiliotis; Paul Sugarbaker (Gastroenterology Research and Practice, 2012)
The management and the outcome of peritoneal metastases or recurrence from epithelial ovarian cancer are presented. The biology and the diagnostic tools of EOC peritoneal metastasis with a comprehensive approach and the most recent literatures data are discussed. The definition and the role of surgery and chemotherapy are presented in order to focuse on the controversial points. Finally, the paper discusses the new data about the introduction of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) in the treatment of advanced epithelial ovarian cancer.